2017
DOI: 10.1016/j.endm.2017.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Additive bases and flows in graphs

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…One example is any Z 5 -flow that uses only values 1 and 2. Esperet, de Verclos, Le, and Thomassé [6] proved that if a graph G is strongly Z 5 -connected, then every orientation D(G) of G admits an antisymmetric Z 5 -flow. Together with work of Lovász et al [13], this implies that every directed 12-edge-connected graph admits an antisymmetric Z 5 -flow.…”
mentioning
confidence: 99%
“…One example is any Z 5 -flow that uses only values 1 and 2. Esperet, de Verclos, Le, and Thomassé [6] proved that if a graph G is strongly Z 5 -connected, then every orientation D(G) of G admits an antisymmetric Z 5 -flow. Together with work of Lovász et al [13], this implies that every directed 12-edge-connected graph admits an antisymmetric Z 5 -flow.…”
mentioning
confidence: 99%
“…The girth condition is reduced to 14 in [11], to 13 in [10], and finally to 12 in [9]. By duality, using the results of Nešetřil and Raspaud [69], the result of Esperet et al [28] together with the theorem of Lovász et al [59] also showed girth 12 suffices. Esperet et al [28] remarked that "it is not known whether the same holds for planar graphs of girth at least 11 after the grith 12 result of Borodin, Ivanova and Kostochka [9] since 2007".…”
Section: Introductionmentioning
confidence: 93%
“…By duality, using the results of Nešetřil and Raspaud [69], the result of Esperet et al [28] together with the theorem of Lovász et al [59] also showed girth 12 suffices. Esperet et al [28] remarked that "it is not known whether the same holds for planar graphs of girth at least 11 after the grith 12 result of Borodin, Ivanova and Kostochka [9] since 2007". Note that, the result of Dvořák and Postle [26] seems not to apply to homomorphism to oriented graphs.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations